Zirconocene-catalyzed copolymerizations of ethylene with 5-methyl-1,4-hexadiene as non-conjugated diene - Jin, YH; Im, SS; Kim, SS; Kwak, S; Kim, KU; Kim, KH; Kim, J (POLYMER SOC KOREA, 2002)
The mixtures of non-conjugated dienes. 4-methyl-1,4-hexadiene and 5-methyl-1,4-hexadiene (MHD), were successfully synthesized by the reaction of isoprene with ethylene using Fe(III)-based catalyst in toluene. The conversion was over 96 mol%, on the basis of the initial amount of isoprene used. The production yield for MHD was nearly 50 mol%, the other was polyisoprene. The mixtures were successfully copolymerized with ethylene by using zirconium-based metallocenes. The products were characterized by the combinations of gas chromatography, high temperature gel permeation chromatography. H-1 NMR. C-13 NMR, high temperature H-1 NMR, UV/Visible spectroscopy, and differential scanning calorimetry. It was found that 5-methyl-1,4-hexadiene was active enough to be incorporated into the copolymer chain but the corresponding isomeric material, 4-methyl-1,4-hexadiene, was inactive in metallocene-catalyzed copolymerizations. Specifically, in the zirconocene-catalyzed copolymerizations of ethylene with MHD, ansa-structure catalysts seem to be more efficient than non-bridged type zirconocene. The degree of incorporation of MHD in the resulting copolymers was able to be controlled by the amount of non-conjugated dienes used initially.
Keywords: METALLOCENE CATALYSTS; OLEFIN POLYMERIZATION; STYRENE; COMBINATION; MECHANISMS; PROPENE